A Comparison between the Tunnel Technique with Autogenous Grafts and Coronally Advanced Flap for Root Coverage of Multiple Gingival Recessions: A Randomized Clinical Trial - Jaber Yaghini; Mehrnegar Mahmoudzadeh; Zohreh Afshari; Amir Farmohammadi; Ahmad Mogharehabed (Frontiers in Dentistry)
Objectives: The purpose of this study was to compare the clinical performance of coronally advanced flap (CAF) with connective tissue graft (CTG) and vestibular incision subperiosteal tunnel access (VISTA).